ANALYSIS OF THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON CORPORATE PERFORMANCE (Empirical Study on Manufacture Companies Listed on Stock Exchanges in Indonesia Periode 2010 - 2012 ) - Wiyan Patria; Rossje V Suryaputri (Jurnal Akuntansi Trisakti, 2014)
The purpose of this study is to determine the influence of corporate social responsibility on corporate performance. Samples were taken as much as 252 which consists of 84 companies listed on the Indonesia Stock Exchange in 2010- 2012. The variables used in this study are (ROE (return on equity), CSR (corporate social responsibility), CAR (Cumulative abnormal returns. DER (debt to equity ratio), SG (Sales growth), Beta, EU (Unexpected earnings ) as control variables.The results Showed that CSR does not have a significant influence on Return On Equity (ROE) as a measurement of financial performance and the company's cumulative abnormal return (CAR) as a performance measurement of the company's market. In the future studies are advised to conduct research with other variables in addition to Corporate Social Responsibility (CSR) which may affect the company's financial performance and corporate markets.